2010
DOI: 10.1007/s11669-010-9819-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Atomic Mobilities in fcc Cu-Fe and Cu-Ti Alloys

Abstract: The experimentally measured diffusion coefficients of fcc Cu-Fe and Cu-Ti alloys in the published literature were reviewed critically in the present work. On the basis of the available thermodynamic information, the atomic mobilities of Cu, Fe, and Ti in fcc Cu-Fe and Cu-Ti alloys as a function of temperature and composition were assessed in terms of the CALPHAD method using the DICTRA Ò software. The optimized mobility parameters are presented. The calculated diffusion coefficients show an excellent agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 49 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Molecular dynamics analysis technology is widely used in the field of computational materials science, and it should be relatively sufficient in characterizing the atomic-scale structure and atomic diffusion behavior of materials [25,26]. Ouyang Yifang et al used molecular dynamics model to analyze the atomic structure of an Fe/Al system and the interdiffusion behavior of Al and Fe, their results indicated that molecular dynamics model could also be used to analyze Cu/Fe system [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics analysis technology is widely used in the field of computational materials science, and it should be relatively sufficient in characterizing the atomic-scale structure and atomic diffusion behavior of materials [25,26]. Ouyang Yifang et al used molecular dynamics model to analyze the atomic structure of an Fe/Al system and the interdiffusion behavior of Al and Fe, their results indicated that molecular dynamics model could also be used to analyze Cu/Fe system [27,28].…”
Section: Introductionmentioning
confidence: 99%